Population structure and relative growth of rock snails Reishia bitubercularis (Gastropoda: Muricidae) from Ambon Island, Eastern Indonesia - Muhammad Masrur Islami; Francy Nendissa; Daniel Josef Tala, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
The present study reports and discusses population structure and morphometric relationships of muricid Reishia bitubercularis in two populations from Ambon Island, Maluku. Field sampling was conducted at two locations with typical hard substrate i.e. Ambon Bay and Central Maluku, where each location comprises three different stations. Morphometric relationships were analyzed for shell dimensions i.e., shell length (SL), shell width (SW), shell height (SH) and total weight (TW). A total of 496 individuals of R. bitubercularis were collected in both locations. SL ranged from 7.07 to 42.38 mm in Ambon Bay, and 12.45 to 42.69 mm in Central Maluku. The highest number of individuals in Ambon Bay and Central Maluku was in size 26-28 mm and 30-32 mm, respectively. The mean SW/SL ratio ranged from 0.67 mm to 0.73 mm. Sex ratio was significantly different from 1:1, with females outnumbered males in both locations. Morphometric relationships indicated SL grows faster than SW in both locations and faster than SH and TW in Central Maluku. While the growth rate between SL vs SH; and TW vs SL are relatively similar in Ambon Bay. Overall, both Ambon Bay and Central Maluku have a similar variation of abiotic factors which also play an important role in shell morphometrics and relative growth of muricids, especially related to the exposed area in the rocky intertidal zone where sampling was conducted.